Perceived Barriers Of Evidence-Based Practice Among Nurses Working In Qazvin Hospitals - Mohammad Zakaria Kiaei; Mohammad Azmal; Faramarz Kalhor; Elham Shah Bahrami; Rohollah Kalhor (Tehran University of Medical Sciences, 2016)
Background and Aim: Nurses’ main tasks include the provision of healthcare services at the highest levels of quality and quantity standards, and based on the findings of scientific research. The aim of the present study is to identify and determine the barriers of evidence-based practice among nurses of Qazvin hospitals, in Iran, at 2013. Materials and Methods: The present cross-sectional research was a descriptive- analytic study conducted among 260 nurses practicing in six hospitals of Qazvin in 2013. The barriers scale questionnaire developed by Funk, et al. was used to examine the four dimensions of evidence-based practice (EBP) barriers including adopter, organization, innovation and communication characteristics. To analyze the data, descriptive and analytic statistics were used. Results: The mean score of EBP barriers among subjects was 3.07 out of 4. Among the barriers, "organization" and "adopter" dimensions had the highest and lowest mean scores, respectively. There was no significant statistical relationship between gender and EBP performance, But a significant relationship was observed between organizational dimension with age, employment type and work experience. Conclusion: Since “organization” was found to be the main  barrier to  the use of research in nursing performance, policy-makers and administrators should pay attention to the use of research in performance, the establishment of a research culture in organization, the creation of appropriate infrastructures, and the allocation of sufficient time to the nursing personnel to have access to evidences.